The Cancer Handbook 2007
DOI: 10.1002/9780470025079.chap35.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cavity and Major and Minor Salivary Glands

Abstract: Cancer of the oral cavity is almost synonymous with squamous cell carcinoma as 90% of cancers in the oral mucosa appear to be of this type. The sixth most common oral malignancy is the different types of adenocarcinoma arising from salivary glands. A small proportion of cancers in the oral cavity are composed of melanoma, lymphoma, and various types of sarcomas. Oral squamous cell carcinoma is the sixth common malignancy and is a major cause of cancer morbidity and mortality worldwide. Although the aetiology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Such mutations have been identified in 46% of patients with head and neck cancer [ 45 ], and have been identified by direct sequencing in 67% of saliva samples from OSCC patients [ 45 , 46 ]. The p53 gene, which is located on chromosome 17p13.1, exhibits mutation in 50–70% of epithelial tumours [ 47 , 48 ]. Loss of heterozygosity of the p53 allele has been reported in 22% of cases of pre-cancer and 20% of oral cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mutations have been identified in 46% of patients with head and neck cancer [ 45 ], and have been identified by direct sequencing in 67% of saliva samples from OSCC patients [ 45 , 46 ]. The p53 gene, which is located on chromosome 17p13.1, exhibits mutation in 50–70% of epithelial tumours [ 47 , 48 ]. Loss of heterozygosity of the p53 allele has been reported in 22% of cases of pre-cancer and 20% of oral cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of heterozygosity of the p53 allele has been reported in 22% of cases of pre-cancer and 20% of oral cancer. Other genes related to p53 and the cell cycle, such as p16, p27, p63, and p73 have been found to be altered to varying degrees in oral cancer [ 47 , 48 ]. Using plaque hybridisation, Boyle et al [ 48 ] identified tumour-specific p53 mutations in 71% of saliva samples from patients with head and neck cancer.…”
Section: Resultsmentioning
confidence: 99%
“…9 Other genes such as p16, p27, p63, p73 related to p53, and cell cycle are altered in varying degrees in oral cancer. 10 Main functional activity of p53 is cell cycle arrest and initiation of apoptosis in response to the DNA damage.…”
Section: The Salivary Genomic Markersmentioning
confidence: 99%
“…[ 32 ] Other genes such as p16, p27, p63, p73 related to p53, and cell cycle are altered in varying degrees in oral cancer. [ 33 ]…”
Section: The Salivary Tumor Markers In Oral Cancermentioning
confidence: 99%